Enhancing Investment Climate through Integrated Border Management: A Case Study of The Riau Islands Border Zone - Priangani, Ade; Windary, Shylvia (Journal of Indonesian Social Sciences and Humanities, 2022)
As an Indonesian province adjacent to Singapore and Malaysia, the Riau Islands is also strategically a foreign investment center. Unfortunately, ongoing challenges in border management, from inter-agency coordination to cumbersome customs procedures and insufficient infrastructure, undermine its investment appeal. Border efficiency and investment climate will be the idea of this research under an IBM (Integrated Border Management) scheme in Riau Islands cities such as Batam, Bintan and Karimun. This study tackles three central research question as following; What are the main problems of border management in Riau Islands? and What are the IBM principles that can apply here as things we must be putting in practice to overcome these challenges? Method: To address these questions, the study uses qualitative research methodology, combining in-depth interviews with government officials and policy analysts as well as local business leaders with document analysis of regional border and trade policies. The results indicate the constraint of coordination of Indonesian border agencies, absence of effective bilateral formulary with Singapore and Malaysia become main issues affecting efficient delivery/serving at the borders. A two-tiered IBM will be proposed in this study: firstly on strengthening the Indonesian agencies to enable national integration to reduce operational burden and bureaucratic delay; secondly on the international collaboration with neighbouring countries to improve cross-border mobility and ensuring security. As a result, the application of IBM will optimize transit time, lower administrative cost and provide certainty in the regulation applies so that Riau Islands could be more appealing to foreign investors. This indicates that an IBM is not only required for border security but also a strategic instrument for regional economic development.